(untitled) (Global Journal of Medical Research, 2022)
It is well known that the new coronavirus pandemic (COVID-19) is absolutely the biggest public health emergency the world has been facing in recent years. In addition to concerns about physical health, it also brings concerns about the psychological suffering that may be experienced by the general population and by the health professionals involved. The aim of this study was to demonstrate knowledge about implications for mental health and psychological interventions in view of the new coronavirus pandemic. A review of the technical-scientific literature produced in different countries was carried out, with a view to understanding recent advances related to COVID-19. Results are presented on the implications of the pandemic on mental health, and guidance on psychological interventions, considering particularities of the general population and health professionals. Finally, potentialities and challenges for the practice of psychologists in the Brazilian context during the pandemic and neuropsychology in the post-pandemic world are discussed: patient vs. neurotherapist challenges.